Atendimento a homens autores de violências contra as mulheres: desafios à articulação das políticas de Segurança Pública e às políticas sociais em Belo Horizonte 3 Minas Gerais - Miriam Aparecida Mendes (2022)
The present work has gender violence as its central theme, focusing on the needs of intervention strategies and actions with men who are authors of violence against women. In this sense, the proposal of the study was to analyze the challenges and possibilities of building network actions aimed at education, reflection and accountability of men who are perpetrators of domestic and family violence against women in the Center for Crime Prevention, Central Program for Monitoring Criminal Alternatives (CEAPA) in Belo Horizonte / MG. This project, called Acción de Responsabilización de Hombres Autores de Violencia contra la Mujer en el ámbito de la Ley Maria da Penha, is carried out in reflective groups with men who are authors of violence against women sent by the Judiciary. The project seeks to understand how to confront the phenomenon of violence against women, seeking accountability, dialogue, and reflection with men, as recommended by article 45 of the Maria da Penha Law. Based on the theoretical basis related to the themes of male domination, masculinities, subjective rectification, articulation of network services and multisectoral public policies, it is understood that violence is multifaceted, and its combat must involve the whole society, since the increasing violence does not come only from delinquency or simply violent acts, but are related to structural machismo, patriarchy and gender inequality still present in the culture. As for the methodological aspects, the research, qualitative in nature, took place in two stages: in the first, we carried out participant observation of twelve meetings with men who were perpetrators of violence against women; the second took place with semi-structured interviews with the professionals who work with the men. From information previously obtained with the professionals who perform the group actions or individual consultations with these subjects. The analysis of the methodologies and interventions carried out with the perpetrators of violence against women, as well as the realization of the stages of the research, allowed the understanding that interventions with male perpetrators of violence against women can not be isolated actions of the Public Security Policy, but that interlocutions with local policies are necessary, especially with health and social assistance, so that there is confrontation and prevention of gender violence effectively.